Relating remotely sensed forest damage data to wind data: storms Lothar (1999) and Vivian (1990) in Switzerland - Usbeck, Tilo; Waldner, Peter; Dobbertin, Matthias; Ginzler, Christian; Hoffmann, Christian; Sutter, Flurin; Steinmeier, Charlotte; Volz, Richard; Schneiter, Gustav; Rebetez, Martine (My University, 2012)
This study compares the surface wind speed and forest damage data of two exceptionally severe winter storms, Vivian 1990 and Lothar 1999. The study area comprises the region that suffered damage in Switzerland. The wind speed data were derived from simulations of MeteoSwiss (Federal Office of Meteorology and Climatology), measurements during the storm periods and expert analyses of the data. The remotely sensed forest damage data were provided by the Federal Office for the Environment and the forest cover data by Swiss Federal Statistical Office. We compared data on the peak gust and maximum average wind speed, with data on the spatially related forest area and forest damage area, and found some clear differences in the correlations between the different wind data and forest damage. Our results point generally to the damage-causing role of near-surface gusts at maximum wind speeds during the storm. These tended to be spatially distributed on a fine scale. In only a few cases were the results statistically significant. However, these results could probably be improved with better wind data. For example, gust measurements spatially closer to forests or simulations of gusts at maximum wind speed could be produced with a spatially higher resolution.